Scales SOFA and qSOFA as prognosis of mortality in patients diagnosed with sepsis from a Peruvian clinic: Escalas SOFA y qSOFA como pronóstico de la mortalidad en pacientes con diagnóstico de sepsis de una clínica peruana - Scarsi-Mejia, Ottavia (2022)
Introduction: Sepsis is a clinical condition that seriously threatens the body’s balance and is still a significant cause of death. Therefore, clinical management is aimed at a timely classification and implementation of emergency measures based on systems of scales for detection that helps reduce complications in patients. That is the importance of using SOFA (Sequential Organ Failure Assessment) and qSOFA (quick SOFA) in the different services for hospitalized patients. Objective: To evaluate the usefulness of SOFA and qSOFA scale as a predictor of mortality in patients with sepsis hospitalized in the intensive care unit (ICU) of the Good Hope Clinic from January to December 2015. Materials and methods: Retrospective study of adult patients hospitalized in ICU/NICU with sepsis diagnoses. Epidemiological, clinical, and laboratory data were collected to apply the SOFA and qSOFA scales. We performed a description of the variables studied, an analysis of the variables, and the scoring systems compared in the ROC curve. Results: The main infectious focus was respiratory (41.5%). The patients died was 28.3%. The variables serum creatinine and lactate were statistically significant with OR = 11.67 (95% CI 2.58-52.85, p<0.001) and OR = 5.78 (CI 95% 1.45-23.03, p = 0.009), respectively. The AUC for SOFA was 0.698, p = 0.026, 95% CI (0.54-0.85), showing to be statistically significant. A cutoff point of 7.5 was found with a sensitivity of 46.7% and 86.8% specificity. QSOFA did not show a statistically significant association. Conclusions: The SOFA scale showed a probability of death in patients with sepsis admitted to ICU/NICU.